Seasonal variation of bone turnover markers in top-level female skiers - Lombardi, G.; Colombini, A.; Freschi, M.; Tavana, R.; Banfi, G. (European Journal of Applied Physiology, 2011)
Different levels of weight-bearing activities imply different levels of anabolic effects on skeletal tissue and this can be assessed by measuring biochemical markers reflecting bone metabolism. With this study we wanted to determine how the serum levels of bone turnover markers change during different phases of annual training in elite female skiers. Fourteen top-level Caucasian athletes, from the Italian Women`s Alpine Ski Team (slalom and giant slalom), were tested at the end of the relative rest period (T1), the pre-competitive season (T2) and the competitive season (T3). Serum levels of bone-specific alkaline phosphatase (BAP) and tartrate-resistant acid phosphatase (TRAP5b) activities and of osteocalcin (OC), and crosslaps (the carboxyterminal crosslinked telopeptide of type I collagen—ß-CTx), were assayed together with the determination of 25(OH)D levels. The formation markers, BAP and OC and the resorption marker TRAP5b significantly increased from T2 to T3, while crosslaps showed no significant changes. The peculiar trends of bone formation markers correlated one to each other at T2 versus T3, and this was probably linked to the highly demanding period of competitions when, in athletes performing weight-bearing exercise, bone is more stimulated by mechanical forces. 25(OH)D levels, instead, changed from T1 to T2 and from T1 to T3 and its trend do not show any correlation with that of bone markers. In conclusion, we found that both the bone formation markers and TRAP5b, marker of resorption, are significantly increased from the pre-competitive season to the competitive season.